Relationship of Smoking Habits to The Potential of Hydrogen (pH) of Saliva in Active Smokers - Purbasari, Euis; Erikardo, Oktadio; Jasmine, Rifa Audia (Sean Institute, 2022)
Tobacco smoke when smoking contains harmful chemicals for the body, such as nicotine, tar, carbon monoxide, and others. These toxic substances enter the body and increase cancer risk, chronic obstructive pulmonary disease, cardiovascular disease, and teeth and mouth. The oral cavity is the organ first exposed to cigarette smoke. There is a liquid to maintain oral health, namely saliva, with an average Potential of Hydrogen (pH) of around 6.8-7.4. Saliva acts as a buffer to keep the salivary pH to remain neutral. The buffer capacity can decrease due to the influence of cigarette smoke, which spreads throughout the oral cavity and will be followed by a decrease in salivary pH to become more acidic. This will affect the function of saliva in maintaining the health of the oral cavity from caries, halitosis, dry mouth, and others. This study aimed to investigate the relationship between smoking habits and salivary pH in active smokers. This study used an analytic survey with a cross-sectional research design approach. The sample is 30 respondents with a purposive sampling technique. Results: there is a significant relationship between the number of cigarettes consumed per day (p=0.009) and the duration of smoking (p=0.004) on salivary pH. Conclusion: An increase in smoking habits in terms of the number and time of tobacco has a relationship with a decrease in salivary pH.